Comparing Latin American nutrient profile models using data from packaged foods with child-directed marketing within the Brazilian food supply - Borges, Camila Aparecida; Khandpur, Neha; Neri, Daniela; Duran, Ana Clara (Frontiers in Nutrition, 2022)
Objectives: To examine and compare the extent to which different nutrient profile models (NPM) from Latin America (LA) identify child-directed marketing at packaged foods and beverages sold in Brazil, as being high in nutrients linked to risk of non-communicable diseases (NCDs). Materials and Methods: This cross-sectional study evaluated 3,464 foods found in the five largest Brazilian supermarkets. Child-directed marketing was coded using the International Network for Food and Obesity/NCDs Research, Monitoring and Action Support (INFORMAS) protocol. Differences in medians of sugar, saturated fats and sodium per 100 kcal in foods with the presence and absence of child-directed marketing, were tested using the Mann-Whitney test. We compared six NPMs in LA and examined to what extent they targeted these products using prevalence ratios. Analyses were performed overall and by the degree of food processing according to the Nova food classification. Results: We found 1,054 packages with child-directed marketing. Among these, candies, cakes and pies, sauces and creams, and sugar-sweetened beverages were significantly higher in sugar, saturated fat, and sodium per 100 kcal compared with products no target at children (p<0.05). Compared to the PAHO and the Mexico models, the Brazilian NPM would allow 3 times more ultra-processed foods to omit warnings for sodium (p<0.05). The Uruguayan NPM also flagged fewer ultra-processed foods high in sodium (p<0.05). The Brazilian model compared to Mexico and PAHO also allow 4 times more sugar-sweetened beverages and 6 times more dairy drinks to omit warnings for sugar. In comparison to all other NPMs, the Brazilian model showed the worst performance in identifying baked goods as high in sodium. The models of Chile, Uruguay, and Peru would also target significantly less sugar-sweetened beverages high in at least 1 critical nutrient, than PAHO and Mexico. Conclusion: Compared to other NPMs in LA, the NPM criteria adopted in Brazil is more permissive and less likely to inform consumers of the poor nutritional quality of ultra-processed foods and beverages with child-directed marketing.